Synthesis and Charact'erizatio.n of new Schiff base ligand [(2-{1-[(2 hydraxyÂ benzylidene)-hydrazono]-ethyl} benzene-I, 3, 5--triol.] and it's CQmp.lexes. with Co en\ Ni . (U),, cÂ·u(U)' and Â· zn(II). - T.Numan, A.Â· (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The eaction  of 2 4 .6-trihydroxyactophenonemonohydra1e  withl hydr.azine monohydrate was realized tiÂ·nder reflu.(( in methanol and i:l.Jew drops of glacial acetic acid we.re added to give lhe'(int rmediate)2-(1hydr pno-ctbyt)-benzcne-Â·1.3.5-r:Qql,       which      reacted     wittlsaEcy.laldehyde. jn methm)ql to gjy;e 'a new :tyRe CNzOi) Ligand  (H:flL]f(2-{1-[(2-=bydroxy-bertzylideÂ·ne)-bydrazqoo,J-eÂ·thy.1}bcnzeÂ·neJ ;3Â·,5of trio] . The ligand wa,-, reacted with Mct2 (whereÂ·     M=Co. Ni, CU., :and ttl') under ,refltiX in met11a11l  with t-1 :1) rati.o ro give complexes     t:lie genera[ fomn.da [)\;4  (HzLJl.  All' comppunds have been c'hrn;'C\c.tedzed by  spec_ troscopic methpds  [1H  1\;fMR  IR. U.V-Vis;  BPLC. atomic absorp ion]  mi.croanalys1s along  w:ith Ctllnductivity   rneasu.r []1er.n: From the above .datÂ· (he prpposedÂ· molecular struc;LI,.Ire for reo (I f2I.)]., [Cu (H.2:L)],                     -                                                                                        .JZn. CH2L)] complexes may adopt a tetrahedraL struct\!Jre. While  squ;uplanar geometry  was sugge,stcd foT  Ni (IJ) complex.